Parallel coding of moving images using fractals - Andonova, S.; Popovic, D.; Kowalzik, M.; Behrmann, M.; Janneck, J. (IEEE First ICA³PP, IEEE First International Conference on Algorithms and Architectures for Parallel Processing, Brisbane, Australia, 19-21 April, 1995, 1995)
A parallel fractal-based algorithm for predictive coding of a sequence of images is presented. The first frame in the sequence is fractal coded and transmitted. Each next frame is obtained as a motion compensated prediction by geometrically transforming the previous frame. The difference between the actual new frame and its prediction is fractal coded and transmitted to the receiver, in order to be used for the new frame reconstruction. A former-worker parallelization concept is used for parallel implementation of the computationally very extensive fractal-based video coding.< >